Anacardiaceae - Machado, Natalia Candido (Arquivos do Museu Nacional, 2021)
A taxonomic study of Anacardiaceae species found at the Restinga de Jurubatiba National Park, Rio de Janeiro, Brazil, revealed that there are three genera and three species: Anacardium ocidentale L., Schinus terenbinthifolia Raddi, and Tapirira guianensis Aubl. The species are described; an identification key is given, together with illustrations, geographic distribution, and comments on each species.